2015
DOI: 10.1159/000439525
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Levels and Nicotine Dependence: A Cross-Sectional Study and Clinical Trial

Abstract: Background: High oxidative stress, which is caused by smoking, can alter omega-3 fatty acid concentrations. Since omega-3 fatty acids play a role in dopaminergic neurotransmission related to dependence, it is important to understand their effects on nicotine dependence. Methods: This research comprised 2 studies. The first one consisted of a cross-sectional evaluation, in which the levels of the most important omega-3 fatty acids, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), were compared betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 34 publications
(74 reference statements)
2
19
2
Order By: Relevance
“…Humans dependent on opiates or nicotine often consume a lipid-poor diet resulting in low plasma DHA levels [55, 56]. These DHA-deficient diets alter the DHA content of specific brain regions, decrease membrane fluidity and the expression of multiple pre- and post-synaptic proteins [5760].…”
Section: Discussionmentioning
confidence: 99%
“…Humans dependent on opiates or nicotine often consume a lipid-poor diet resulting in low plasma DHA levels [55, 56]. These DHA-deficient diets alter the DHA content of specific brain regions, decrease membrane fluidity and the expression of multiple pre- and post-synaptic proteins [5760].…”
Section: Discussionmentioning
confidence: 99%
“…Geographical and cultural patterns could induce a routinely different intake of foods rich in omega-3. A dietary deficiency of omega-3 may be associated with an increased risk of smoking [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The omega-3 fatty acids are important components of cell membranes and have a role in numerous human metabolic processes [ 1 ]. These substances may contribute to the prevention and treatment of neurological [ 2 , 3 ] and cardiovascular diseases [ 4 6 ], many chronic inflammatory and respiratory diseases [ 7 10 ], several of which are also linked to tobacco smoking [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on tobacco dependence have shown that smokers have decreased levels of blood DHA [ 35 , 36 ] and clinical trials demonstrated that daily administration of fish oil capsules decreased the dependence and craving levels of smokers [ 36 , 37 ]. Among cocaine-dependent individuals, studies have shown that low levels of fatty acids are related to relapse vulnerability and aggression [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%